Field survey and analysis of water flux and salinity gradients considering the effects of sea ice coverage and rubber dam: a case study of the Liao River Estuary, China - Hu, Zhanming; Guo, Kaiyuan; Yang, Yongjun; Zhang, Mingliang (Frontiers in Marine Science, 2023)
Predicting net river fluxes is important to promote good water quality, maritime transport, and water exchange in estuaries. However, few studies have observed and evaluated net water fluxes to estuaries under complex conditions. This study used advanced survey techniques to obtain high-frequency monitoring data of cross-sectional current velocity, water level, and salinity in the Liao River Estuary (LRE) from 2017 to 2020. The net water flux into the sea was computed based on field data and the impacts of the rubber dam and sea ice cover on water flux and salinity processes were analyzed in the study region. In the Liao River Station (LRS), the fluctuations of water level and discharge were not obvious in winter due to the sea ice cover. There were significant seasonal and inter-annual changes in water fluxes due to variability in river discharge and tidal oscillations. The results also showed that the net water flux into the sea from the LRS was positive in wet season, and greater during ebb tides than flood tides. The net water fluxes in the normal and dry seasons were mostly negative due to the influence of tides, indicating that the annual runoff from the Liao River fluctuated greatly throughout the year. The water flux in the LRS was more suitable for representing water flux into the sea than the Liujianfang Hydrometric Station (LHS) in the LRE. The impacts of the rubber dam and Panshan Sluice on water fluxes to the sea were both significant. Lower salinity in the study area coincided mostly with height water fluxes to the sea and periods when the rubber dam was raised. This study results provide us new insights to measure the water flux into sea under the condition of ice cover in the tidal reach of estuary and the method can be used for water flux observation for other estuaries.